Implementation of the Partnership Model of the Upstream Oil and Gas Industry Using CSR and Stakeholder Theory (Partnership Practices in Governance in Pertamina EP Zone 7) - Andhar Lutfi; Kurniawati Kurniawati (Journal of Social Research, 2023)
So far the partners involved in CSR at Pertamina tend to be limited, and the relationship between partners and companies and between partners is also less than optimal. Starting from these problems, this study aims to: (i) evaluate partnership practices at Pertamina EP Zone 7, whether they follow the CSR partnership pattern or a partnership pattern based on stakeholder theory; (ii) analyze the extent to which there is equality in partnership practices between stakeholders in Pertamina EP Zone 7; and (iii) analyze how the strategy for expanding the scope of stakeholders in the partnership pattern is by stakeholder theory in Pertamina EP Zone 7. The research approach is qualitative. The research location is Pertamina EP Zone 7. The primary data collection technique is through in-depth interviews, while the secondary data collection technique is through library research. The data analysis technique uses stakeholder theory. The results of the study show that Pertamina EP Zone 7 follows the partnership pattern more than the CSR partnership pattern. There are differences in the intensity of cooperation in the partnership pattern, so Pertamina EP Zone 7 treats the ten partners unequally. Pertamina EP Zone 7 can expand the scope of stakeholders in a partnership pattern that is by stakeholder theory by using the dimensions of the business perspective, the dimensions of the scope of responsibility, and the dimensions of the direction of responsibility.